Effect of fat, oil and grease (FOG) on the conversion of lignite to biogenic methane. (1st January 2023) - Song, Bo; Xia, Daping; Guo, Hongyu; Dong, Zhiwei; Wang, Yongjun; Zhao, Weizhong; Chen, Zhenhong
Graphical abstract: Highlights: The anaerobic fermentation of FOG and lignite promotes their transformation into biomethane. FOG enriches the substrates available to the microbial community. The addition of FOG to the substrates can change the composition and structure of both bacterial and archaeal communities. This study has demonstrated potential for the utilization of lignite and the treatment of FOG. Abstract: The biogenic methane production experiment of FOG combined with lignite was performed to enhance the methane output of lignite anaerobic fermentation. Three-dimensional fluorescence, gas chromatography-mass spectrometry, volatile fatty acids and 16S rDNA tests were carried out to analyze the composition of the liquid substances at the biomethane peak production. The results showed that the yield of this compound in the combined fermentation of lignite and FOG could be increased by 380.25 %. Moreover, the degradable organic matter and acetic acid content increased, while the degree of humification decreased. In addition, the microbial activity was enhanced. In the combined substrate of the anaerobic fermentation process, both Acinetobacter and Methanosarcina were activated as the dominant bacteria and archaea, respectively, which improved the degradation efficiency of organic matter and the overall biomethane yield. This research showed that the combined anaerobic fermentation of FOG and lignite could promote the biomethane production efficiency in the context of anaerobic fermentation, which provided a new idea for the clean transformation of lignite and utilization of FOG.